Neutrophils: From Inflammatory Bowel Disease to Colitis-Associated Colorectal Cancer - Chen T; Liu J; Hang R; Chen Q; Wang D (Journal of Inflammation Research)
Tianyi Chen,1 Jiachen Liu,2 Ruyi Hang,1 Qian Chen,1 Dong Wang1,3 1Cancer Center, Daping Hospital, Army Medical University, Chongqing, People’s Republic of China; 2Radiology Department, Daping Hospital, Army Medical University, Chongqing, People’s Republic of China; 3Oncology Department of Qianjiang Center Hospital, Chongqing University, Chongqing, People’s Republic of ChinaCorrespondence: Dong Wang, Cancer Center, Daping Hospital, 10 Changjiang Zhi Road, Yuzhong Dist, Chongqing, 400042, People’s Republic of China, Tel +86-23-68757151, Fax +86-23-68894062, Email dongwang64@hotmail.comAbstract: Inflammatory bowel disease (IBD) is a non-specific inflammatory disease of digestive tract, primarily manifesting as ulcerative colitis (UC) and Crohn’s disease (CD). The precise etiology of IBD remains elusive. The interplay of genetic factors, environmental influences, and intestinal microbiota contributes to the establishment of an uncontrolled immune environment within the intestine, which can progressively lead to atypical hyperplasia and ultimately to malignancy over a long period. This colorectal malignant tumor that arises from chronic IBD is referred to as colitis-associated colorectal cancer (CAC). Dysregulation in the quantity and functionality of neutrophils plays a significant role in the onset, progression, and recurrence of IBD, as well as in the transition from IBD to CAC. Neutrophils affect the pathophysiology of IBD through various mechanisms, including the production of reactive oxygen species (ROS), degranulation, the release of inflammatory mediators and chemokines, and the formation of neutrophil extracellular traps (NETs). These processes can induce DNA mutations, thereby facilitating the development of colon cancer. Given the incomplete understanding of the disease mechanisms underlying IBD and CAC, effective treatment and prevention strategies remain challenging. Consequently, a comprehensive review of the functional roles of neutrophils in IBD and CAC is essential for advancing our understanding of IBD pathogenesis and identifying potential therapeutic targets.Keywords: inflammatory bowel disease, colitis-associated colorectal cancer, neutrophil, neutrophil extracellular traps